Customer-oriented behaviour of front-line service employees: The need to be both willing and able - Narumon Pimpakorn (2018)
The purpose of this study is to empirically test and extend our knowledge of the determinants of customer-oriented behaviour of front-line employees across a range of service settings. We examine the need for front-line employees to be both 'willing' (engaged) and 'able' (confidence in their ability) in order to deliver high-quality customer service. Since the organisational environment in which workers operate is known to impact job performance, we include service climate as a third explanatory variable in our model. The research hypotheses are tested using self-report data collected from 878 front-line employees in four service industries, covering both medium and high-contact settings. The results support the notion that to deliver excellent customer service, employees must be both 'willing' (engaged, positive attitude) and 'able' (possess the capability, or at least the confidence, to do so). In addition, service climate (an organisation environment factor), employee demographics, and industry type were found to be significant. Finally, the interaction effects of being 'willing' and 'able' are significant in explaining customer-oriented behaviour of front-line employees. © 2010 Australian and New Zealand Marketing Academy.